Revisiting Putnam's two-level game theory in the digital age: domestic digital diplomacy and the Iran nuclear deal. Issue 1 (2nd January 2018) - Bjola, Corneliu; Manor, Ilan
Abstract: Few studies to date have investigated the impact of digitalization on Putnam's two-level game theory. Such an investigation is warranted given that state and non-state actors can employ digital tools to influence decision-making processes at both national and international levels. This study advances a new theoretical concept, Domestic Digital Diplomacy, which refers to the use of social media by a government to build domestic support for its foreign policy. This model is introduced through the case study of the @TheIranDeal twitter channel, a social media account launched by the Obama White House to rally domestic support for the ratification of the Iran Nuclear Agreement. The study demonstrates that digitalization has complicated the two-level game by democratizing access to foreign policy decisions and increasing interactions between the national and international levels of diplomacy.